Expression of Apoptosis Related and Proliferative Proteins in Malignant Lympho-Proliferative Disorders - Zeeba Jairajpuri; Rekha Ghai; Sumita Saluja; Sujala Kapur; K.T Bhowmick (Iranian Society of Pathology, 2017)
Background & objective: The current study aimed to perform an immunohistochemical analysis of patterns of apoptotic and cell proliferative related protein expression in different histological grades and immune phenotypes of malignant lymphomas and other lymphoproliferative disorders Methods:This observational study was carried on 60lymph node biopsies of lymphoproliferative disorders. The biopsies were analyzed histologically and immunohistochemically. Results:A total of 60 lymph node biopsies were included in the study, of which 81.6% were of malignant lympho-proliferative lesions. The majority of the biopsies were B-cell (66%) and were grouped in the intermediate grade. Bax and BCL-2 protein expression was presented by percentage of immune positive neoplastic cells per 10fields and graded on a scale of 1 to4. A Bcl-2, Bax Protein Ratio (BBPR) was determined for each case by dividing the estimated Bcl-2 protein (percentage of Bcl-2 positive cells x Bcl-2 staining intensity) by the estimated Bax protein (percentage of Bax positive cells x Bax immunostaining intensity). The mean BBPR was found to be significantly higher in indolent lymphomas (2.64 ± 1.3) as compared to aggressive lymphomas (0.47 ± 0.9) (P<0.01). The expression of P53 and PCNA in 35 biopsies of Non Hodgkin Lymphomas (NHL) was found to increase from low to high grade tumors. Conclusions: A significant correlation was found between BBPR and predicted biological behavior of indolent and aggressive lymphomas. This indicates the important role of Bcl-2 and Bax in biological behavior of lymphomas. Furthermore, P53 and PCNA expression were found to increase from low to high-grade tumors suggesting their prognostic value in NHL.